2018
DOI: 10.1177/0898264318820448
|View full text |Cite
|
Sign up to set email alerts
|

Hilliness and the Development of Walking Difficulties Among Community-Dwelling Older People

Abstract: Objective: The objective of this study is to study the associations of objectively defined hilliness with the prevalence and incidence of walking difficulties among community-dwelling older adults, and to explore whether behavioral, health, or socioeconomic factors would fully or partially explain these associations. Method: Baseline interviews ( n = 848, 75-90 years) on difficulties in walking 500 m, frequency of moving through the neighborhood, and perceived hilliness as a barrier to outdoor mobility were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…These results are in line with earlier observations (23,24). In addition, our earlier studies showed that perceiving hilliness as an outdoor mobility barrier predicted maladaptive walking modifications, i.e., reducing the frequency of walking or giving up walking (22) and that steeper roads in the home neighborhood predicted the development of walking difficulties (53). In the current study, the lower number of PA bouts and fewer MVPA minutes observed among older adults who live surrounded by a steep road network, supports the earlier finding that steep slopes hinder the daily walking of older adults.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in line with earlier observations (23,24). In addition, our earlier studies showed that perceiving hilliness as an outdoor mobility barrier predicted maladaptive walking modifications, i.e., reducing the frequency of walking or giving up walking (22) and that steeper roads in the home neighborhood predicted the development of walking difficulties (53). In the current study, the lower number of PA bouts and fewer MVPA minutes observed among older adults who live surrounded by a steep road network, supports the earlier finding that steep slopes hinder the daily walking of older adults.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we expect that for individuals facing functional decline, perceiving facilitators for outdoor mobility may increase their likelihood of using adaptive walking modifications and decrease their likelihood of using maladaptive walking modifications. In contrast, environmental demands that exceed a person’s capacity are risk factors for physical inactivity and the development of functional limitations over time (Keskinen et al, 2018a; Portegijs et al, 2017b; Rantakokko et al, 2011). Previous studies have shown that environmental barriers to outdoor mobility, such as poor street conditions or lack of resting places, are associated with restricted outdoor mobility (Rantakokko et al, 2015; Tsai et al, 2013) and increased the risk for developing walking difficulty over time (Keskinen et al, 2018a; Rantakokko et al, 2016).…”
mentioning
confidence: 99%
“…In contrast, environmental demands that exceed a person’s capacity are risk factors for physical inactivity and the development of functional limitations over time (Keskinen et al, 2018a; Portegijs et al, 2017b; Rantakokko et al, 2011). Previous studies have shown that environmental barriers to outdoor mobility, such as poor street conditions or lack of resting places, are associated with restricted outdoor mobility (Rantakokko et al, 2015; Tsai et al, 2013) and increased the risk for developing walking difficulty over time (Keskinen et al, 2018a; Rantakokko et al, 2016). Thus, we expect that perceiving environmental barriers to outdoor mobility may especially be associated with the use of maladaptive walking modifications and increased risk for adopting maladaptive walking modifications over the follow-up among those not reporting such modifications at the baseline.…”
mentioning
confidence: 99%
“…Musculoskeletal pain might be one of the causes of depressive symptoms [ 38 ]. In addition, it may be possible that the hilly environment discourages older adults with musculoskeletal pain from going for long walks [ 39 ]. As older adults with musculoskeletal pain had less physical activity and manifested more sedentary behavior, the lifestyle might cause depressive symptoms [ 33 , 40 ].…”
Section: Discussionmentioning
confidence: 99%